Assessment of pharmacovigilance activities among pharmacist interns in Nigeria: a cross-sectional study - Shadrach Chinecherem Eze; Evaristus Chinonso Odoh; Kingsley Chinemerem Eze; Wisdom Enyinnaya Arugo; Gerald Obinna Ozota; Ugomma Loveth Anyaji; Chidimma Elizabeth Mbakamma; Collins Chukwuemeka Magbo; Samuel Chijioke Ofili; Victor Chikaodiri Amaechi; Chimaobi Jude Nwiyi; Joy Chekwube Onyesoro; et al. (SpringerOpen, 2023)
Abstract Background Pharmacovigilance (PV) and adverse drug reaction (ADR) reporting is at the core of the services and functions of a pharmacist. Pharmacist interns undergoing their one-year mandatory internship program are expected to be armed with this tool kit in order to provide adequate pharmaceutical services in all areas of pharmacy practice. Objectives This study sought to assess the knowledge and perception of pharmacovigilance and adverse drug reaction reporting among pharmacist interns in Nigeria. Methods This study was a cross-sectional study among pharmacist interns in their one-year mandatory internship program across Nigeria. The 32-item semi-structured questionnaires were administered online using simple random sampling with the snowballing technique to recruit the participants in the study. The results were analyzed with IBM SPSS version 25. Descriptive statistics were used to summarize the data. The Chi-square test and contingency coefficient were used to determine the association between knowledge of PV and the demographics of the participants. Results A total of 450 pharmacist interns participated in this study. The participants' knowledge of pharmacovigilance and ADR is 92.5%. About 96.2% of respondents feel that responses to newly released pharmaceuticals must be recorded, compared to 79.1% for older drugs already on the market. There is a high correlation between the duration of the internship program and understanding of PV and ADR reporting among participants. More than fifty percent of respondents concur that ADR reporting is critical, while more than eighty percent concur that ADR reporting is required for pharmacists, the most significant health professionals in ADR reporting. The participants' length of participation in an internship program and their internship location significantly impact their opinion of ADR reporting. Seventy-four percent (74%) of respondents from tertiary hospitals say their internship center encourages ADR reporting. Conclusion Most participants have a solid understanding of PV and ADR reporting, but perceptions of PV and ADR reporting are substantially correlated with internship location and program length. Active measures should be implemented to ensure that all pharmacy interns comprehend and embrace PV and ADR reporting as their exclusive duty.